1996
DOI: 10.1055/s-0038-1650625
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cellular Binding Sites and Interactive Regions within Reactants Required for Enhancement of Plasminogen Activation by tPA on the Surface of Leukocytic Cells

Abstract: SummaryPlasminogen and tPA bind to a common set of binding sites on nucleated cells. To assess the functional consequences of cellular binding, we have measured the kinetic changes induced by plasminogen activation by tPA on cell surfaces. These studies were carried out with U937 and THP-1 monocytoid cells, with Raji, Nalm6 and Molt4 lymphoid cells and with peripheral blood monocytes and neutrophils. The interactions of plasminogen and tPA with cells induced an increase in the rate of plasmin generation which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 34 publications
7
94
0
Order By: Relevance
“…These cells have previously been characterized for binding of plasminogen, uPA and tPA (8,9,31,32). In the present detailed study, the levels of stimulation with fulllength glycosylated tPA were up to 30 -80-fold, which is as good as or better than observed in previous studies with cells or isolated receptors or heparin or fibrinogen fragments (5, 21).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…These cells have previously been characterized for binding of plasminogen, uPA and tPA (8,9,31,32). In the present detailed study, the levels of stimulation with fulllength glycosylated tPA were up to 30 -80-fold, which is as good as or better than observed in previous studies with cells or isolated receptors or heparin or fibrinogen fragments (5, 21).…”
Section: Discussionsupporting
confidence: 62%
“…For example, the tPA receptor annexin II, which binds tPA with a K d of 48 nM, is capable of producing modest stimulation of enzyme activity (Ͻ10-fold) in vitro (7). Monocytes and monocytoid cells have been studied and found to bind tPA with a low affinity, but high capacity, and are able to stimulate tPA enzyme activity up to around 20-fold (8,9). Other receptors on liver cells have also been investigated in an attempt to understand the structural features of tPA, both protein and carbohydrate, involved in receptor binding and responsible for its short in vivo half-life and rapid clearance from the circulation when tPA is administered as a thrombolytic agent (10).…”
mentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33] Independent studies also have implicated externalized α-enolase and GAPDH on mammalian and pathogen surfaces as sites for plasminogen binding and subsequent activation by host or pathogen activities, [26][27][28]30,31,[34][35][36] and we have demonstrated that externalized glycolytic enzymes on the apoptotic cell surface, including α-enolase, also are sites for plasminogen binding. 12 Although enhanced virulence has been attributed to the presumptive augmentation in mobility through matrix or fibrin clots associated with localized plasminogen activation following binding on the pathogen surface, 37,38 no compelling physiological rationale exists for plasminogen binding on non-invasive bacteria and apoptotic cells.…”
Section: Box 1 the Repertoire Of Innate Apoptotic Immunity Early Transupporting
confidence: 57%
“…Then 20 nM single-chain recombinant human t-PA (Genentech, South San Francisco, CA) was added. Plasmin activity (expressed as OD 405 nM) was measured after 6 min by diluting the reaction mixture 1:10 into S-2251 (DiaPharma Group, Franklin, OH) to a final concentration of 1 mM and monitoring absorbance at 405 nM as described previously (Felez et al, 1996).…”
Section: Methodsmentioning
confidence: 99%